Bacteria‐Targeted MRI Probe‐Based Imaging Bacterial Infection and Monitoring Antimicrobial Therapy In Vivo. Issue 44 (23rd September 2021) - Li, Linyao; Gu, Peilin; Hao, Mengqi; Xiang, Xiaoli; Feng, Yuting; Zhu, Xiaokang; Song, Yang; Song, Erqun
Abstract: Despite the significant advances of imaging techniques nowadays, accurate diagnosis of bacterial infections and real‐time monitoring the efficacy of antibiotic therapy in vivo still remain huge challenges. Herein, a self‐assembling peptide (FFYEGK) and vancomycin ( Van ) antibiotic molecule co‐modified gadolinium (Gd) MRI nanoaggregate probe (GFV) for detecting Staphylococcus aureus ( S. aureus ) infection in vivo and monitoring the treatment of S. aureus‐ infected myositis by using daptomycin ( Dap ) antibiotic as model are designed and fabricated. The as‐prepared GFV probe bears Van molecules, making itself good bacteria‐specific targeting, and the peptide in the probe can enhance the longitudinal relaxivity rate ( r 1 ) after self‐assembly due to the π–π stacking. The study showed that, based on the GFV probe, bacterial infections and sterile inflammation can be discriminated, and as few as 10 5 cfu S. aureus can be detected in vivo with high specificity and accurately. Moreover, the T1 signal of GFV probe at the S. aureus ‐infected site in mice correlates with the increasing time of Dap treating, indicating the possibility of monitoring the efficacy of antibacterial agents for infected mice based on the as proposed GFV probe. This study shows the potential of GFV probe for diagnosis, evaluation, and prognosis of infectious diseases in clinics. Abstract : The T1 ‐weighted magnetic resonance imaging probe (GFV), composed of Gd 3+ as T1 signal unit, vancomycin as target ligand, and self‐assembling peptide (FFYEGK) for signal enhancement, is successfully employed to specifically and sensitively detect Staphylococcus aureus ( S. aureus ) infection in mouse myositis model and monitor antimicrobial therapy in vivo, indicating the great potential for bacterial infectious disease diagnosis and prognosis.